Pemanfaatan Media Pembelajaran Dalam Meningkatkan Literasi Fisika Materi Kalor SMAN 2 Monta - Trisnawati, Ice; Subhan, Muhammad; Suswati, Lis (Universitas Nggusuwaru, 2025)
Literacy is the ability of an individual to process and understand information while engaging in reading and writing during learning activities. The type of research employed in this study is a quasi-experimental study with a control group pretest‑posttest design. The population of the study comprises all 54 tenth‑grade students at SMA Negeri 2 Monta. The sampling technique used was random sampling. The research instrument for data collection was a test measuring students’ achievement in physics. The data analysis technique employed was the t‑test. The data analysis for the experimental class revealed that, on the pre-test, the highest score was 95, the lowest score was 45, with an average of 69.07, while on the post-test, the highest score was 100, the lowest score was 55, with an average of 81.48. In contrast, for the control class, the pre-test scores showed a highest score of 85, a lowest score of 40, and an average of 64.44; for the post‑test, the highest score was 95, the lowest score 45, with an average of 71.85. The results of the questionnaire analysis indicate that the utilization of learning media is highly beneficial in developing students’ physics literacy. The inferential statistical test (t‑test) produced a t‑value of 4.204, which is greater than the t‑table value of 2.160. This result means that the t‑value is higher than the t‑table value; consequently, the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted. Based on these findings, it can be concluded that the utilization of learning media has an effect on improving physics literacy in the topic of heat among students at SMA Negeri 2 Monta for the academic year 2023/2024